Phenotypic characterization of sweet potato (Ipomoea batatas L.) genotypes in Ethiopia for selection of those possessing optimal dual-purpose - Selamawit Abebe Gitore; Benjamin Danga; Sylvia Henga; Fekadu Gurmu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
This research mainly focuses on the morphological characterization of genotypes of sweet potatoes present in Ethiopia for the selection of those with optimum dual-purpose (as food and feed characteristics). From August to December 2019, alpha lattice design using two replication was performed under field condition for this experiment. At 90 days and 180 Days After Planting (DAP), morphological characterization of the 40 sweet potato varieties based on 16 vine, leaf characters and storage root descriptors was performed. In order to exclude those that clearly did not meet the minimum appropriate value of the descriptors provided for selecting dual-purpose cultivars, field observational yield trials were conducted using CIP descriptors. The data generated in this study, using RSTUDIO software, Agricole kit, Partially Balanced Incomplete Block (PBIB), test function, were subject to Variance Analysis (ANOVA). The substantially different mean values were compared using the Tukey test at the p< 0.05 stage. Cluster and main component analyses were both conducted using SPSS software (version 20.0). There were major differences among the 40 varieties in almost all of the leaf, vine and root characters examined except Central Leaf Lobe (CLL), Petiole Length (PL) and Storage Root Cortex Thickness (SRCT). Calculations based on root to vine ratio formulas were used to classify dual-purpose use varieties. When the 40 sweet potato genotypes were also tested for dual-purpose use, the analysis found significant phenotypic diversity using the data from the calculation and analyzed data from morphological descriptors. Varieties with R/V values in the 0.2-0.3 range are recommended as dual-purpose high forage varieties, whereas those with R/V values in the 0.3-0.55 range are graded as dual-purpose high root varieties. As a result, 30 varieties can be recommended as dual-purpose based on the root/vine ratio.